SERUM HOMOCYSTEINE AS A RISK FACTOR FOR CORONARY HEART DISEASE - Naureen, Ayesha; Munazza, Bibi; Shaheen, Robina; Khan, Shahbaz Ali; Fatima, Fozia (Journal of Ayub Medical College Abbottabad, 2012)
Background: Homocysteine (Hcy) is an intermediate formed during the catabolism of sulphur containing essential amino acid, methionine and Less than one percent of tHcy is found as the free form. Development of atherosclerotic changes and thrombo-embolism are common features in patients with homocysteinuria. This study was conducted to assess the relationship of Hcy and coronary heart disease (CHD) in our population. Methods: The cross-sectional analytical study was carried out at the Department of Biochemistry, Hazara University Mansehra and Ayub Medical College, Abbottabad. A total of 80 subjects were included in this study and were divided into 2 groups. Cases Group consisted of 40 patients who had confirmed Myocardial Infarction (MI) coming for routine follow-up (first re-visit) after the acute attack. Control Group consisted of 40 matching healthy individuals. Demographic data including age, gender, dietary habits, height and weight as documented in preformed proforma. Blood pressure was taken in sitting posture. Serum total Hcy were measured. Data was entered into computer using SPSS 16.0 for analysis. Results: The mean age of the cases was 59.68±8.06 (30-70) years and that of the controls was 58.93±6.93 (48-76) years. The average BMI of cases was 27.70±3.61 Kg/m2 and of the controls was 25.66±2.98 Kg/m2. This increase of BMI from controls to cases was statistically significant (p<0.050). The mean systolic BP of the cases was 153.88±11.90 mmHg in comparison with 142.62±11.65 mmHg for the controls. This difference was statistically significant (p<0.001). Mean tHcy level of the cases was 17.15±4.45 Î¼mol/l while that of controls was 12.20±2.53 Î¼mol/l. There is a statistically significant difference between cases and controls with respect to Hcy levels (p<0.001). Conclusion: Plasma tHcy level has a powerful predictor value of CHD and routine screening for elevated Hcy concentrations is advisable especially for individuals who manifest atherothrombotic disease without their traditional risk factors. Keywords: Hyperhomocysteinemia (HHcy), coronary heart disease (CHD)